Management and outcome of cutaneous diphtheria in adolescent refugees in Germany, June 2022 - October 2023 - Zink, Alicia; Hofer, Juliana; Schneider, Christian; Kessler, Franziska; Klenze, Hannes; Klauwer, Dietrich; Maleki, Klaudia; Müller, Andreas; Goretzki, Sarah; Wang, Shubei; Kobbe, Robin; Ramirez, Andrea Vanegas; et al. (Infection, 2024)
Objectives: From September 2022 an increase in Corynebacterium diphtheriae (C. diphtheriae) infections was reported in Europe. Our study focuses on 31 adolescent and young adult refugees with cutaneous C. diphtheriae infections detected in Germany. We examined treatment regimens and outcomes to provide targeted insights into the management of this infection. Methods: We distributed a standardized survey, focused on children and adolescents presenting to paediatric clinics through the German Paediatric Infectious Diseases Society (DGPI) and additional professional contacts in Germany. Data were extracted from routine medical documentation and reported anonymously. Results: A total of 31 individuals with cutaneous C. diphtheriae infection were reported by 9 centres. Two of these showed diphtheria toxin (DT) related systemic symptoms and four exhibited systemic inflammation requiring complex management. The remaining 25 cases, with exclusively cutaneous manifestations, were afebrile. Treatment with topical antiseptics and systemic antibiotics, mainly aminopenicillin/beta-lactamase inhibitors (BLI) (35%) or clindamycin (25%), achieved eradication in all but two cases treated with aminopenicillin/BLI. Treatment duration varied between 5 and 17 days. Conclusions: In refugees presenting with chronic skin wounds, C. diphtheriae should be included into the differential diagnosis. Fever seems to be a valuable marker to differentiate severe cases with potentially DT-mediated sequelae from exclusively cutaneous diphtheria (CD). For afebrile CD, topical antiseptics and oral antibiotic therapy with clindamycin for 7 days, followed by clinical surveillance appears to be a safe treatment regimen. Patients with CD who present with fever or pharyngitis should be thoroughly investigated including blood and pharyngeal swab cultures.
Gesehen am 08.11.2024